Comparing prospective hydrogen pathways with conventional fuels and grid electricity in India through well-to-tank assessment. (12th May 2022) - Chugh, Sachin; Chaudhari, Chinmay; Sharma, Alok; Kapur, G.S.; Ramakumar, S.S.V.
Abstract: The present study uses Greenhouse Gases, Regulated Emissions, and Energy Use in Technologies Model (GREET), to compare hydrogen generated via multiple pathways (Natural gas, methanol reforming; coal, petcoke, biomass gasification etc) with the conventional fuels like diesel and compressed natural gas and grid electricity under Indian context through a comprehensive well to tank assessment based on net CO2 equivalent emission and energy consumption. Limited availability of customized studies comparing hydrogen production and supply with other energy options in India distinguishes the present work as it provides a fresh insight into potential pathways for hydrogen production while assessing feedstock availability and raw water consumption. The study reveals that biomass gasification and solar electrolysis are among the least GHG emitting pathways to fill one unit of energy equivalent in the tank. Hydrogen produced through natural gas reforming is 70% less emission intensive and 38% more energy efficient than Indian grid electricity. Graphical abstract: Image 1 Highlights: GHG and energy consumption of conventional fuels at WTT stage in Indian context. WTT emissions and energy consumption for multiple hydrogen pathways for India. Mapping raw water consumption for various hydrogen pathways. Assessing importance of solar and bio-based pathways for H2 production.